Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1194/jlr.m800027-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma PCSK9 preferentially reduces liver LDL receptors in mice

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a secreted protein that regulates the expression of LDL receptor (LDLR) protein. Gain-of-function mutations in PCSK9 cause hypercholesterolemia, and loss-offunction mutations result in lower plasma LDL-cholesterol. Here, we investigate the kinetics and metabolism of circulating PCSK9 relative to tissue levels of LDLRs. The administration of recombinant human PCSK9 (32 mg) to mice by a single injection reduced hepatic LDLRs by ?90% within 60 min, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
165
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(186 citation statements)
references
References 32 publications
13
165
4
1
Order By: Relevance
“…Veh, vehicle; NS, not significant. expression (37,54,55). Although it has been reported that TM induces the VLDLR via the PERK-ATF4 pathway (13), the potential mechanisms by which TM affects LDLR expression are numerous.…”
Section: Discussionmentioning
confidence: 99%
“…Veh, vehicle; NS, not significant. expression (37,54,55). Although it has been reported that TM induces the VLDLR via the PERK-ATF4 pathway (13), the potential mechanisms by which TM affects LDLR expression are numerous.…”
Section: Discussionmentioning
confidence: 99%
“…Although hepatocyte-specific transgenic mice weakly overexpressing PCSK9 (3-fold) exhibit no significant change in circulating LDL-cholesterol, a ϳ30-fold overexpression increased it by ϳ5-fold (20). Data from transgenic mice expressing very high levels of human PCSK9 in mouse kidney (35) or liver (16), or continuous infusions of recipient WT mice with recombinant PCSK9 (36) indicated that Ͼ100 nM amounts of circulating PCSK9 are required to affect liver LDLR protein levels significantly, without affecting extrahepatic LDLR. In that context, we recently showed that annexin A2 inhibits the effect of extracellular PCSK9 on LDLR, and in view of its absence from hepatocytes in vivo, it may exert its inhibitory effect in extrahepatic tissues (14).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the low plasma LDL-C levels and the reduction of CHD displayed in PCSK9 loss-of-function mutation carriers, which seem furthermore healthy, indicate that the inhibition of PCSK9 should be an effective target in the treatment of hypercholesterolemia with no known adverse side effects. The recent elucidation of the crystal structure of PCSK9 [Cunningham et al, 2007;Piper et al, 2007], especially in complex with the LDL receptor [Kwon et al, 2008], should provide essential clues for the identification of small pharmacological molecules or antibodies that might block the interaction of PCSK9 and the LDLR and thus inhibit PCSK9 function and constitute new cholesterol-lowering drugs [Kwon et al, 2008;Grefhorst et al, 2008].…”
Section: Future Prospectsmentioning
confidence: 99%